Василий III: исторический роман : в 2-х книгах / В. И. Артамонов - Артамонов Вадим Иванович (Советский писатель, 1991)
Экземпляры: аб. (1991) / Инвентарный номер: 33759 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44